Сборник задач и упражнений по органической химии - Морозова В. М.; Седов А. М.; Васильева В. П.; Халфина И. Л.; Буркаева Л. Е.; Жучков В. П.; Новиков А. Н. Автономий Николаевич (Томск, Изд-во ТПИ, 1967)
Ротапринт ТПИ.